Deskriptif Proses Pembuatan Alat Musik Rabab Pasisia di Painan Timur Kabupaten Pesisir Selatan - Aulia Pratama Ricardo; Wimbrayardi Wimbrayardi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The process of making traditional musical instruments Rabab Pasisia in South Pesisir Regency. This study aims to describe the process of making Rabab Pasisia musical instruments. The approach used is a qualitative approach with a descriptive type of research. This research was conducted with data collection techniques used are observation, interview and documentation techniques. Data analysis techniques are carried out by reducing, presenting data and verifying this data aims to find out the structure, process, manufacturing techniques, playing techniques, from Rabab Pasisia. This musical instrument is made of jariang wood and has different tones, and uses several types of wood. The results of this study show that the parts and stages of the process of making traditional Rabab Pasisia musical instruments include: wooden mangkapatiah for Rabab bodies, sketching rabab patterns, making rabab tongues, installing rabab friction nylon, making rabab kudo-kudo, and how to produce sounds, tuning systems on traditional Rabab Pasisia musical instruments. The instruments used in the process of making traditional musical instruments Gandang Tambua include: Lantiak Knife (containing rabab tongue), Kapatiah (forming rabab body), Cutting Saw, Hammer (Stick), Measuring instrument (meter), Pencil, Sandpaper, Scissors. The ingredients are; Jariang Wood (45Cm Long, 30Cm Wide, and 4Cm Thick), Montiah Wood (Meranti), Sicerek Wood, Shell, Rope, Nails and, Wood glue. The process of making Rabab Pasisia musical instruments includes several stages, namely: 1) The process of making the body (jariang wood), until the finishing of fine and rough sanding, 2) The process of installing nylon on the rabab frictioner, 3) The process of installing squirrels, kudo-kudo, talingo and rabab strings for tuning the tone.